Review of non-ionized electromagnetic waves effects on human parasites: a systematic review - Eslamirad, Zahra; Soleimani, Homa (Journal of Liaquat University of Medical & Health Sciences, 2024)
So far, various natural and synthetic compounds have been used to treat and control parasites and their diseases, but now researchers have turned to mechanical and physical methods. This study aimed to review and categorize studies in which non-ionizing electromagnetic waves were used to control or treat human parasites. A systematic search was conducted. All English or full Persian articles on the investigation of electromagnetic waves on worms (Helminths) and protozoan parasites worldwide (from 1970 to 2023) indexed in Google Scholar, Science Direct, PubMed, Scopus, Medline, Medlib, Scientific Information Database, ProQuest, IranMedex, IranDoc, Embase and Magiran were collected and reviewed. Finally, 53 articles were included in the study. Its information was extracted and organized in tables based on the kind of non-ionizing wave. The results of this study categorized the information obtained from the articles based on the type of non-ionizing waves and parasites. The findings of this study may serve as a guide for researchers as they create and execute future studies. This review study exposed the capability of non-ionizing electromagnetic waves to inactivate, control and treat parasitic diseases. This review revealed gaps in this field of study, and a road map was provided to design and implement new projects.